Comparison of normalized maximum aerobic capacity and body composition of Sumo wrestlers to athletes in combat and other sports - Beekley, M. D.; Abe, T.; Kondo, M.; Midorikawa, T.; Yamauchi, T. (Journal of Sports Science & Medicine, 2006)
Sumo wrestling is unique in combat sport, and in all of sport. We examined the maximum aerobic capacity and body composition of sumo wrestlers and compared them to untrained controls. We also compared "aerobic muscle quality", meaning VO2max normalized to predicted skeletal muscle mass (SMM) (VO2max /SMM), between sumo wrestlers and controls and among previously published data for male athletes from combat, aerobic, and power sports. Sumo wrestlers, compared to untrained controls, had greater (p < 0.05) body mass (mean ± SD; 117.0 ± 4.9 vs. 56.1 ± 9.8 kg), percent fat (24.0 ± 1.4 vs. 13.3 ± 4.5), fat-free mass (88.9 ± 4.2 vs. 48.4 ± 6.8 kg), predicted SMM (48.2 ± 2.9 vs. 20.6 ± 4.7 kg) and absolute VO2max (3.6 ± 1.3 vs. 2.5 ± 0.7 L·min-1). Mean VO2max /SMM (ml·kg SMM-1·min-1) was significantly different (p < 0.05) among aerobic athletes (164.8 ± 18.3), combat athletes (which was not different from untrained controls; 131.4 ± 9.3 and 128.6 ± 13.6, respectively), power athletes (96.5 ± 5.3), and sumo wrestlers (71.4 ± 5.3). There was a strong negative correlation (r = - 0.75) between percent body fat and VO2max /SMM (p < 0.05). We conclude that sumo wrestlers have some of the largest percent body fat and fat-free mass and the lowest "aerobic muscle quality" (VO2max /SMM), both in combat sport and compared to aerobic and power sport athletes. Additionally, it appears from analysis of the relationship between SMM and absolute VO2max for all sports that there is a"ceiling" at which increases in SMM do not result in additional increases in absolute VO2max.